Leadership Style and Quality Control System on Managerial Performance in a Public Accounting Firm: Mediated Balanced Scorecard Measurement - Rusyad Nurdin; Hakim, Luqman; Galib, Septemberizal (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This research aims to examine the influence of transformational leadership style and quality control system on managerial performance with balanced scorecard measurement as a mediation in public accounting firms in the DKI Jakarta region. The research is based on the numerous public accounting firms that have been sanctioned by regulators, raising questions about the aspect of managerial performance. The study is grounded in agency theory as accountability in decision-making and contingency theory as the management role in a public accounting firm's organization. The research is quantitative with primary data from the population of auditors in public accounting firms in the DKI Jakarta region. The sample was selected using purpose sampling, and a total of 120 auditors were chosen. The research technique involves descriptive statistics using the SEM-PLS 4.0 tool. The research results yield two conclusions. The first model indicates that transformational leadership style partially influences balanced scorecard measurement, quality control system partially influences balanced scorecard measurement, transformational style partially influences managerial performance, quality control system partially influences managerial performance, and balanced scorecard measurement influences managerial performance. The second model shows that quality control system is mediated by balanced scorecard measurement influences managerial performance. Meanwhile, transformational leadership style mediated by balanced scorecard measurement does not influence managerial performance.